Культурно-мистецькі листи до художниці Ольги Плешкан - Павчак, С. (Україна: культурна спадщина, національна свідомість, державність, 2012)
Опубліковано з відповідним коментарем листи до української художниці Ольги Плешкан (1898–1985) від її колег – учнів мистецької школи О. Новаківського. Автор отримав їх від О. Плешкан на початку 1980-х рр. і публікує вперше. Ці листи є одним із джерел для дослідження культурно-мистецького (малярського) життя на Західній Україні в 1920–1930‑х рр. The letters to the Ukrainian artist Olha Pleshkan (1898-1985) from her colleagues, the students of Novakivskyi’s art school, are published in the article with corresponding commentaries. The author of the article received these letters from Pleshkan at the beginning of the 1980s and publishes them for the first time. These letters represent a source of research of cultural and artistic life in the Western Ukraine in the 1920s–1930s.